Circumcision in subject with hemophilia: the Yogyakarta Method - Widjajanto, Pudjo Hagung; Hadi, Nurul; Saputro, Ivan Onggo; Wibowo, Agus; Budiono, Nur; Tusino, Agus; Sutowo, David Wijaya (Indonesian Pediatric Society, 2024)
Background Circumcision is one of the most common surgical procedures in boys in Indonesia. In cases patient with hemophilia (PWH), doctors tend to avoid this procedure due to increased bleeding tendency. In 2007, we developed a protocol for clotting factor concentrate (CFC) administration for circumcision in SWH, namely, the “Yogyakarta Method.” Objective To evaluate the outcomes of the Yogyakarta Method for circumcising PWH. Methods This descriptive study was based on medical records of PWH who underwent circumcision at Dr. Sardjito Hospital (DSH), Yogyakarta and 3 surrounding hospitals under DSH supervision from 2008-2017 and 2018-2022. Diagnoses of hemophilia were based on clinical findings and factor assays. Subjects with hemophilia A received factor VIII (25 IU/kg/dose) and those with hemophilia B received factor IX (50 IU/kg/dose) before, during and after the procedure. In addition, patients received tranexamic acid (15 mg/kg/dose). Circumcision was performed by a pediatric surgeon or urologist. Results From 2008-2017, 28 PWH underwent circumcision, 14/28 of whom were in DSH. Twenty-six patients had hemophilia A and 2 had hemophilia B. Their severities were mild (12 subjects), moderate (10), and severe (6). Subjects’ median age was 10.5 (5-19) years and their median CFC use was 8 (range 7-10) doses in hemophilia A and 4 (range 4-5) doses in hemophilia B patients. Three of 28 PWH had bleeding episodes after the procedure. Following the encouraging results from the initial 2008-2017 study period, most of PWH circumcised in 2018-2022 underwent the procedure in the same 3 district hospitals rather than at DSH (21/28 subjects), and had similar CFC consumption. Only 1 bleeding episode occurred after the procedure during the second study period. Conclusion The Yogyakarta method is safe and sufficient to control bleeding in circumcision of PWH. This method is also suitable in a district hospital setting.